2017
DOI: 10.1038/s41598-017-05850-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of the floral transition in Rosa chinensis ‘Old Blush’ and R. odorata var. gigantea

Abstract: The floral transition is a crucial developmental event, but little is known about the underlying regulatory networks in seasonally and continuously flowering roses. In this study, we compared the genetic basis of flowering in two rose species, Rosa chinensis ‘Old Blush’, which flowers continuously, and R. odorata var. gigantea, which blooms in early spring. Gene ontology (GO) terms related to methylation, light reaction, and starch metabolism were enriched in R. odorata var. gigantea and terms associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
5
21
0
Order By: Relevance
“…In this work, many DEGs and DEPs were identified between the two types of pineapple, namely, CP and SC, which are categorized as Queen and Cayenne, respectively, before the ethephon induction treatment, which suggested that there are basic differences between CP and SC. Similar results occurred in the reports of the seasonal and continuous flowering roses in response to floral transition [34] as well as for low-and high-cadmium-accumulating genotypes of pakchoi (Brassica chinensis L.) in response to cadmium stress [35]. In particular, the results revealed that the expression levels of the ETR and ERF genes were lower in CP than in SC before the ethephon induction treatment, whereas those of the ACS and ACO genes were higher.…”
Section: Variation In the Basic Ability Of Ethylene Signal Transductisupporting
confidence: 75%
See 2 more Smart Citations
“…In this work, many DEGs and DEPs were identified between the two types of pineapple, namely, CP and SC, which are categorized as Queen and Cayenne, respectively, before the ethephon induction treatment, which suggested that there are basic differences between CP and SC. Similar results occurred in the reports of the seasonal and continuous flowering roses in response to floral transition [34] as well as for low-and high-cadmium-accumulating genotypes of pakchoi (Brassica chinensis L.) in response to cadmium stress [35]. In particular, the results revealed that the expression levels of the ETR and ERF genes were lower in CP than in SC before the ethephon induction treatment, whereas those of the ACS and ACO genes were higher.…”
Section: Variation In the Basic Ability Of Ethylene Signal Transductisupporting
confidence: 75%
“…Increases in soluble sugar concentrations in the apical meristem represent one of the first physiological changes in plants and sugar and starch metabolism play vital roles in the regulation of the floral transition [34,40]. In the present work, the expression of the SPS, FBP and BAM genes and of some sugar metabolic proteins (GluPAT and BGLU) were upregulated and were found to be higher in CP than in SC after ethephon application.…”
Section: Expression Of Floral Induction-related Degs and Deps Respondmentioning
confidence: 58%
See 1 more Smart Citation
“…Clustering pattern analysis of gene expression is commonly used in transcriptome research [34][35][36]. However, we found that some DEGs identified by clustering pattern in this study were differentially expressed in both cultivars of P. rockii, which limited the identification of specific factors.…”
Section: Wgcna Of Carpel Quantitative Variation In P Rockiimentioning
confidence: 59%
“…RNA-seq technology is an important method to obtain effective functional genes in crops, especially for crops without reference genomic information. At present, RNA-seq has been widely used to study floral organ development in woody plants [32][33][34][35][36]. With the development of highthroughput sequencing technology, numerous studies have been carried out by SMLRS or in combination with NGS technology.…”
Section: Introductionmentioning
confidence: 99%